1988
DOI: 10.1523/jneurosci.08-03-01039.1988
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in Ca2+/calmodulin-dependent protein kinase II in cultures of hippocampal pyramidal neurons and astrocytes

Abstract: We have analyzed Ca2+/calmodulin-dependent protein kinase II (CaM-kinase II) localization, activity, and endogenous protein substrates during differentiation and synaptogenesis in cultured hippocampal neurons. Primary cultures from hippocampi from 18 d embryonic rats are composed primarily of pyramidal neurons, with minimal contamination by nonneuronal cells. We have used monoclonal (Mab) and affinity-purified polyclonal antibodies that recognize either or both of the subunits of CaM-kinase II in order to loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 58 publications
9
48
0
Order By: Relevance
“…The apparent requirement for ␣CaMKII expression is consistent with the reported low levels of Ca 2ϩ /calmodulin-stimulated protein phosphorylation in 2 DIV cultures of hippocampal neurons (Scholz et al, 1988).…”
Section: Discussionsupporting
confidence: 86%
“…The apparent requirement for ␣CaMKII expression is consistent with the reported low levels of Ca 2ϩ /calmodulin-stimulated protein phosphorylation in 2 DIV cultures of hippocampal neurons (Scholz et al, 1988).…”
Section: Discussionsupporting
confidence: 86%
“…No expression was observed in large striatal neurons or non-neural cell types. This neuronal cellular pattern of expression is in keeping with the known expression patterns of CaMKII (Ouimet et al, 1984;Scholz et al, 1988). Thus, transgene expression occurs in a cellular population similar to that identified for endogenous GDNF (Lopez-Martin et al, 1999).…”
Section: Resultssupporting
confidence: 74%
“…Previous studies have demonstrated the existence of CaMKII in astrocytes (26,28), and CaMKII activated by Ca 2ϩ was shown to phosphorylate vimentin in these cells (19,26). Furthermore, they display local and global Ca 2ϩ signaling in response to neurotransmitters (8,29 (Fig.…”
Section: Spatial Signaling From Ca 2ϩ Via Camkii To Vimentinmentioning
confidence: 88%